KONFLIK BATIN DAN NILAI PENDIDIKAN KARAKTER DALAM NOVEL UMMI UNTUK GAMAL KARYA AQILA NILA - Muhammad Anas; Ali Nuke Affandy; Panji Hermoyo (PENTAS : Jurnal Ilmiah Pendidikan Bahasa dan Sastra Indonesia, 2026)
This study aims to describe the forms of internal conflict experienced by the main character, Insyira (Sisi), in Aqila Nila’s novel Ummi untuk Gamal and their relevance to character education values. Employing a literary psychology approach based on Kurt Lewin’s conflict theory, this descriptive qualitative research utilizes reading and note-taking techniques for data collection. The findings reveal three types of internal conflict: approach-approach (positive–positive), which is the most dominant; avoidance-avoidance (negative–negative); and approach-avoidance (positive–negative). These conflicts reflect the protagonist’s struggle between personal desires, moral obligations, and decision-making ambivalence. Furthermore, the results indicate that these internal dynamics are closely linked to character education values, including religiosity, responsibility, caring, hard work, and independence. It is concluded that internal conflict not only drives the plot but also serves as a vehicle for character building. This novel is highly relevant as a reflective and educative medium in literary learning, particularly for the younger generation.